2013
DOI: 10.4161/hv.22192
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus vaccine uptake, knowledge and attitude among 10th grade students in Berlin, Germany, 2010

Abstract: IntroductionPersisting human papillomavirus (HPV) infections, especially with HPV high-risk types 16 or 18, are prerequisites for cervical precancer and cancer. At the end of 2006 a quadrivalent HPV-vaccine became available in Germany providing protection against the HPV-types 6, 11, 16, and 18. The primary vaccination series consists of 3 separate doses administered at 0, 2, and 6 mo. If an alternate vaccination schedule is necessary, the second dose should be administered at least one month after the first a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
68
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(80 citation statements)
references
References 37 publications
4
68
1
4
Order By: Relevance
“…6 Previously conducted coverage studies from Germany, which were mainly based on survey data, have shown heterogeneous results, depending on the considered age group, region, and study population. [3][4][5]7 Direct comparability of our results with those studies is hampered by different aspects. First of all, an estimation of the vaccination coverage rather than the vaccine uptake was not possible in the context of the present study due to the limited study period (only the year 2008), for which the data was available.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…6 Previously conducted coverage studies from Germany, which were mainly based on survey data, have shown heterogeneous results, depending on the considered age group, region, and study population. [3][4][5]7 Direct comparability of our results with those studies is hampered by different aspects. First of all, an estimation of the vaccination coverage rather than the vaccine uptake was not possible in the context of the present study due to the limited study period (only the year 2008), for which the data was available.…”
mentioning
confidence: 91%
“…6 Vaccination record review (n = 161) including females aged 14-19 y showed an HPV vaccination coverage with all three recommended doses of 41% in the federal state of Berlin. 7 To our knowledge, no comprehensive and nationwide information on the uptake or coverage of HPV vaccination in Germany is available to date. Administrative claims data from health insurances has been shown to be a useful source of data for the monitoring of vaccination coverage or the uptake of newly In Germany, vaccination against human papilloma virus (hPV) has been recommended by the German standing Vaccination committee (sTIKO) for girls aged 12-17 years since March 2007.…”
mentioning
confidence: 99%
“…Bislang liegen für Deutschland keine ausreichenden Erkenntnisse vor, wie hoch die Impfquote ist und in welcher Weise die Inanspruchnahme mit soziodemografischen und versorgungsstrukturellen Faktoren zusammenhängt. Lokale Erhebungen lassen vermuten, dass Bildung und soziales Umfeld einen Einfluss auf die Inanspruchnahme der HPV-Impfung haben [6][7][8]. Für elterliche Impfentscheidungen insgesamt ist bekannt, dass Ärztinnen und Ärzte die Schlüsselfiguren darstellen [9].…”
Section: Hintergrund Und Fragestellungunclassified
“…Mädchen scheinen überwiegend über den Zusammenhang zwischen HPV und Krebs und über die Möglichkeit der Impfung informiert zu sein; allerdings ist der Mehrheit der Befragten die hohe Wahrscheinlichkeit für eine Infektion nicht bewusst [8,27,28]. Immerhin fast 20 % der im Auftrag der BZgA im Jahr 2012 befragten jungen Frauen kannten die HPV-Impfung nicht oder hatten keine Meinung zur Bedeutung der Impfung [5].…”
Section: Wissen Und Einstellungunclassified
“…13,[15][16][17][18][19] Deterrent factors influencing personal decision-making in relation to HPV vaccination have been identified and analyzed and have highlighted, in particular, concerns surrounding vaccine effectiveness and an over-perception of the risk of side effects. [20][21][22] In the analysis of current opposition trends to systematic vaccination, arguments pertaining to the subjective and/or emotional realms allowing for a greater possibility of manipulation, rather than those of scientific evidence, were found. ReseARcH PAPeR 3 times or more.…”
mentioning
confidence: 99%